Kecenderungan Objektivitas Pemberitaan Epidemi Virus H5N1 dalam International Herald Tribune Online - Puspita, Birgitta Bestari (FISIP Universitas Atma Jaya Yogyakarta, 2011)
Abstract: Newspapers have to be objective in representing the news to the audience. This research wanted to measure the objectivityÃ¢â‚¬â„¢s tendency of the news about H5N1 virus, which attacked Indonesia in year 2003. The newsÃ¢â‚¬â„¢ objectivities on International Herald Tribune from January 2005 until December 2006 were being measured with the WesterstahlÃ¢â‚¬â„¢s ObjectivityÃ¢â‚¬â„¢s Principle and content analysis as the method. There are 2 dimensions in WesterstahlÃ¢â‚¬â„¢s ObjectivityÃ¢â‚¬â„¢s Principle. First is factuality, which consists of truth and relevance, and the second one is impartiality which consists of balance and neutral presentation.Ã‚Â Abstrak: Surat kabar harus obyektif dalam menyajikan berita kepada audiens. Riset ini ingin mengukur kecenderungan obyektivitas berita tentang virus H5N1 yang melanda Indonesia pada tahun 2003. Obyektivitas berita diukur berdasar prinsip-prinsip obyektivitas Westerstahl dan menggunakan metode analisis isi. Ada dua dimensi dalam prinsip-prinsip obyektivitas Westerstahl. Pertama adalah faktualitas yang terdiri dari kebenaran dan relevansi, dan yang kedua adalah imparsialitas yang terdiri dari keseimbangan dan penyajian yang netral.